2022
DOI: 10.3389/fmars.2022.866570
|View full text |Cite
|
Sign up to set email alerts
|

A Minimalist Model of Salt-Marsh Vegetation Dynamics Driven by Species Competition and Dispersal

Abstract: We present a new bidimensional, spatially-explicit ecological model describing the dynamics of halophytic vegetation in tidal saline wetlands. Existing vegetation models employ relatively simple deterministic or stochastic mechanisms, and are driven by local environmental conditions. In the proposed model, in contrast, vegetation dynamics depend not only on the marsh local habitat, but also on spatially-explicit mechanisms of dispersal and competition among multiple interacting species. The role of habitat qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 149 publications
(244 reference statements)
0
10
0
Order By: Relevance
“…For example, sites where crab burrowing activity is more intense typically display higher 𝛿 due to the coupling of vegetation disappearance and reduction in local accretion, both aiding in reducing flow resistances and enhancing bottom shear stresses (Crotty et al, 2020;Escapa et al, 2007;Wilson et al, 2022). Besides, environmental changes, which can be significantly accelerated by human activities, can alternate vegetation distributions and biotic activities, thus possibly further modifying site-specific TCN morphological properties (Crotty et al, 2020;Finotello et al, 2022). Rinaldo et al (1999aRinaldo et al ( , 1999b are shown for each study case based on the exceedance probability 𝑃(𝐿 > ℓ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, sites where crab burrowing activity is more intense typically display higher 𝛿 due to the coupling of vegetation disappearance and reduction in local accretion, both aiding in reducing flow resistances and enhancing bottom shear stresses (Crotty et al, 2020;Escapa et al, 2007;Wilson et al, 2022). Besides, environmental changes, which can be significantly accelerated by human activities, can alternate vegetation distributions and biotic activities, thus possibly further modifying site-specific TCN morphological properties (Crotty et al, 2020;Finotello et al, 2022). Rinaldo et al (1999aRinaldo et al ( , 1999b are shown for each study case based on the exceedance probability 𝑃(𝐿 > ℓ).…”
Section: Resultsmentioning
confidence: 99%
“…The inundation stress may lead to smaller biomass production in the poorly drained lower landward areas (Figures 5h and 5l) because of the lower oxygen level (Fivash et al., 2020; Mossman et al., 2020). Furthermore, the modeling approach neglects the dispersal and competitive dynamics between different vegetation species affecting the encroachment of the intertidal platforms (e.g., Finotello et al., 2022), as well as bioturbation by critters. Finally, in the present model, a constant mean sea level is assumed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, biogeomorphological feedbacks, which are key drivers of marsh spatiotemporal evolution, are likely to vary geographically as a consequence of distinct ecological community assemblages and different climatic forcings. This further complicates predicting the morphodynamic effects of salt‐marsh loss, as well as the timescales over which such effects would manifest (Bertness & Ewanchuk, 2002; Finotello, D’Alpaos et al., 2022; Pennings & He, 2021; Wilson et al., 2022).…”
Section: Discussionmentioning
confidence: 99%